STUDI EKSPLORATORI HUBUNGAN ANTARA PENERAPAN LESSCASH SOCIETY DAN KORUPSI (KASUS: SULAWESI TENGGARA - Wiwin Winarlin Sairu (CALYPTRA, 2018)
Corruption has been identified as a complex problem, endemic and is difficult to eradicate. Indonesian has suffered huge losses caused by corruption. Various efforts have been made by Indonesian government to curb corruption. There is a lesscash society policy issued Indonesian Central Bank one of its goals is to curb corruption. This study explores the relationship lesscash society implementation to corruption by using a technique-depth interviews to the civil servants. Assessing the perception of civil servants related to petty corruption, grand corruption or political corruption and practical politics that can be curbed by a policy lesscash society. This study found that lesscash society is able to curb petty corruption, grand corruption or political corruption but unable to curb practical politics in the context of money politics and lesscash society capable of making a payment system to the government of society be sure and improve accountability.